STUDY OF PERINATAL MORTALITY IN TERM BREECH PRESENTATION WITH INCREASING CAESAREAN SECTION RATE - Padmavathi, T.; Aruna (International Journal of Research -GRANTHAALAYAH, 2017)
Breech presentation persists in 3-4% of all term deliveries. There is a threefold increase in perinatal mortality for breech infant delivered vaginally which is related to birth asphyxia and birth trauma. The most frequent cause of death in neonates delivered through breech is intracranial hemorrhage; so many obstetricians recommend caesarean section for breech presentation. It is a retrospective study regarding management of term breech presentation conducted in King George Hospital, Vishakhapatnam from 2012 to 2015 and the results are compared with a similar study conducted in 1981-1984.There is an increase in incidence of caesarean section and decrease in perinatal mortality in our present study when compared to previous study. Increase in caesarean section for breech delivery has decreased the overall incidence of perinatal mortality.